perilaku ibu terhadap pemanfaatan pelayanan kesehatan gigi dan mulut pada anak usia sekolah di SDN 054936 kec.Sei Lepan Kab.Langkat Tahun 2013 - vera ningsih; Eddy Syahrial; Lita Sri Andayani (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTSchool age children are susceptible to oral health problem, SDN 054936 Sub Wonorejo Sei Lepan Langkat District located closest to The Old Village district health center services Sei Lepan. Visits to the school age children oral poly very small and there are many children who have cavities.This study aims to determine the mother’s behavior regarding the use of oral health services to school age children in Elemantary School district 054936 Sei Lepan Langkat district. This type of research is descriptive. The population in this study were 71 mother by using stratified random sampling.The result showed that the use of oral health services school-age children , Mom had a relatively good knowledge (73.3%), attitudes were moderate (60.5%), the belief that good dental and oral health services (97,2%) , distance to the mother's home dental care at the health center less than one kilo meter (69%) , maternal income each month is less than Rp 1.200.000,- (69%), health insurance form JAMKESNAS (69%), support family members were moderate (63.4%) support the husband (23.9%) and 62% did not support family members. The conclusion of this study is largely Mom did not take advantage of dental and oral health services (56.3%) but utilize health services outside the dental and oral health care that is (29.6%). It is therefore expected to be more health centers provide outreach and information to the mother about the importance of dental examination before the advent of dental complaints in children and to take her to participate in monitoring oral health of children and work to improve mother and child visit the dental and oral health services at the health center.